FURTHER RANGE EXPANSION OF THE SCULPTURED RESIN BEE (MEGACHILE SCULPTURALIS) IN SERBIA AND BOSNIA & HERZEGOVINA (Acta Entomologica Serbica, 2021)
Megachile sculpturalis is the first non-native bee species established in Europe, originating from E-Asia. Since early detections in SW-Europe (2008–2010) its spreading resulted in a range currently spanning nearly 2,800 km x 1,100 km across the southern and central Europe. In SE-Europe establishment was confirmed since 2015 in NE-Hungary, followed by detection in N-Serbia (2017), and wider spreading across the eastern Pannonian Plain (2018–2019); eventually it was detected in NW-Bosnia & Herzegovina (2020). Accordingly, the repeated calls for monitoring of M. sculpturalis spread were voiced, aiming to address its potential invasiveness, but mostly lacking a more specific assessment protocol. A 'working concept' for a comprehensive monitoring of M. sculpturalis was proposed within the survey conducted in Belgrade (Serbia) during 2017–2019, based on quantitative assessment of bee population trends in relation to focal plant resources. There was a need to improve and broaden this initial framework, e.g., to allow for different spatio-temporal scales and various potential usage requirements. Therefore, in 2020 we considerably extended the research scope, defined at two spatial scales: LOCAL, for the Belgrade area – the continuation of protocol development, through a high-intensity assessment of M. sculpturalis abundance, bionomics, and distribution, in parallel with assessment of extended set of relevant plants (and potential bee-plant interactions); REGIONAL, a survey covering the bee spreading across Serbia and Bosnia & Herzegovina, aiming to provide a reference time-section in expanding SE-European front, while also extending the knowledge of its environmental affinities. The study included the launching of a pioneering citizen science project, which enabled a remarkable geographic coverage despite modest return of positive reports.The Belgrade-scale survey yielded a modest increase in recorded locations, relative to 2019, but the recording efficiency was decreased, despite a much intensified surveying efforts and extended coverage. This corroborated the importance of inter-seasonal variation of key food resources, which affects both the population dynamics and detectability of this bee, through alternating concentration and dilution effects. We confirmed the strong association of detection success with availability and variability of blooming Styphnolobium, at both scales, indicating the highest relevance of inclusion of this plant into monitoring assessment protocols. The established phenological extent of M. sculpturalis activity (>70 days) also closely corresponded with the phenology of Styphnolobium blooming; yet it does not represent the entire phenological span for the region. Almost no record came from surveying other plants. The regional expansion of M. sculpturalis during 2017–2020 is documented from 19 wider locations (16 added in 2020). It is particularly well established in the Pannonian, and to a lesser extent in peri-Pannonian area of Serbia and B&H, while the approximated range extent was likely doubled during 2019–2020. Further south records were scarce, indicating the slower expansion across the hilly-mountainous part of the Balkans. Records largely came from urban or other settlements, only about a third from semi-natural or agricultural environments.